Adaption of Maximal Glycolysis Rate after Resistance Exercise with Different Volume Load - Nitzsche, Nico; Lenz, Julian Christian; Voronoi, Pjotr; Schulz, Henry (Sports Medicine International Open, 2020)
The aim of this study was to investigate the effect of six-weeks of resistance training with different volume load on the maximum glycolysis rate. 24 male strength-trained volunteers were assigned in a high volume low load (50% of their 1RM with 5 sets and reps up to muscle failure) and a low volume high load (70% of their 1RM with 5 sets of ten reps) resistance exercise group. The resistance training performed 3 days per week over 6 weeks. The maximum glycolysis rate was determined using isokinetic force testing before and after the intervention. There was a significant increase in glycolysis rate over the training period across all subjects (p=0.032). High volume low load exercise increased significantly from 0.271±0.067 mmol·l−1·s−1 to 0.298±0.067 mmol·l−1·s−1 (p=0.022) and low volume high load exercise showed no significant changes from 0.249±0.122 mmol·l−1·s−1 to 0.291±0.089 mmol·l−1·s−1 (p=0.233). No significant effect on glycolysis rate was observed between the training groups (p=0.650). Resistance training increases glycolysis rate regardless of volume load.
Keywords: resistance exercise; lactate; anaerobic power; anaerobic metabolism; muscle adaption